Salmonella sp. as the Cause of Periprosthetic Joint Infection of the Hip: Report of a Rare Case and Review of Past 10-year Literatures - Santoso, Asep; Utomo, Pamudji; Anwar, Iwan Budiwan; Sibarani, Tangkas; Soetjahjo, Bintang; Wardhana, Hanif Andika (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Periprosthetic joint infection (PJI) due to Salmonella sp. is rare. It is sometimes difficult to treat and need prolonged antibiotic treatment. CASE REPORT: We reported a case of PJI of the hip in a 67-year-old female who received prior left total hip arthroplasty. Two-stage revision surgery with antibiotic-loaded cement spacer had been performed to the patient and successfully control the infection. CONCLUSION: Although literature review showed that there has been no consensus for the treatment of Salmonella PJI, a two-stage revision procedure has been more commonly performed to control the infection by previous authors and might be the safest way to control Salmonella PJI recently.